Il Sistema Periodico di Primo Levi come spunto di percorsi didattici interdisciplinari - Funicello, Maria; Chiummiento, Lucia (Chimica nella Scuola, 2024)
The book “Il Sistema Periodico” written by Primo Levi represents certainly a miliar stone in his life and in the life of all the chemistry students. In this brief article it will be represent as for example the tale on the element Carbon could be used to construct educational path for students of superior school of I and II grade.